Clean Water Treatment for Public Health: A Literature Review of Coagulation, Flocculation, Sedimentation, Filtration, and Disinfection Processes - Ramadhan Tosepu; Anggun Anggun; Wa Ode Maulana; Gita Marzan Cahyani; Yuyun Sri Mustika (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Access to clean water is a fundamental right essential for public health, but air pollution by pathogens, heavy metals, and organic particles remains a global risk. Air treatment processes such as conventional coagulation, flocculation, sedimentation, filtration, and disinfection are essential to ensure safe air quality. This study examines the effectiveness of these processes based on current research. Objectives: The purpose of this article is to analyze relevant literature on clean water treatment for public health through a literature review on coagulation, flocculation, sedimentation, filtration, and disinfection. Method: This study uses a systematic literature review method by analyzing 25 related national and international journals from Google Scholar published between 2020-2025. Results: Efficient coagulation reduced turbidity by up to 90% using natural coagulants like moringa oleifera. Sedimentation and filtration removed 95% of microorganisms. Treatment using UV light and chlorine has been shown to reduce the risk of diarrhea by up to 70% in rural areas. Innovations such as nanomaterials are improving the process. Conclusion: Processing. Combining traditional processes with modern technologies is necessary to address the challenges of climate change and urbanization, thus supporting SDG 6 and public health. However, the application of environmentally friendly technologies is necessary to achieve sustainability. Recommendations include regular monitoring and local adjustments. Keywords: Water Treatment, Coagulation, Flocculation, Sedimentation, Filtration, Disinfection, Public Health